Evaluation of Antioxidant Activity of Different Fractions of Melothria maderaspatana - Kumar Balaraman*, Ashok; Singh, Jagadish; Dash, Sasmita; Naskar, Arup; Kumar Maity, Tapan (Asian Journal of Chemistry, 2011)
In the present investigation, fractions of Melothria maderaspatana were tested for their in vitro antioxidant activity. Protocols, such as DPPH radical scavenging assay, lipid peroxidation assay, hydroxy radical scavenging assay, reducing ability, SO radical scavenging assay, were used for evaluation. The strength of fractions and standard drug to scavenge free radicals was inter-compared. The fraction with most promising antioxidant activity was taken for the determination of content of total phenolics and flavanoids. Butylated hydroxy toluene (BHT) and ascorbic acid were used as standard on various occasions in the study. Among all fractions tested, ethyl acetate fraction showed a most significant antioxidant activity. The estimation of total phenolic content and flavonoid content suggested the cause of observed beneficial antioxidant effect associated with the ethyl acetate fraction of M. maderaspatana. The study could lead to a conclusion that the antidiabetic, antilipidemic and antihypertensive activities of this plant could be due to the major contribution of high content of polyphenolics and flavanoids present in ethyl acetate soluble fraction of the plant.